PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL DI KANTOR KEMENTERIAN AGAMA KABUPATEN MUSI RAWAS - Mardhotillah Mardhotillah; Ahmad Basri (LPPM UNIVERSITAS BINA INSAN, 2018)
The aim of this research was to determine the influence of competence and training to the performance of Civil Servants in the Ministry Of Religious Affairs office of Musi Rawas District. The research method was used is quantitativemethod. The population in this research are Civil Servant of Religious Affairs Office of Musi Rawas Regency as many as 204 people and the number of samples are 67 people. Research data was obtained by using questionnaire technique with 15 instrument numbers of statements. Analysis technique was used are t test and F test. From t test result, Competence variable (X1) to performance shows tcount 5,602> ttable 1,997 and sig 0,00 <0,05. Therefore, on partial, competence variable to have an influence a significant impact on the performance (Y) at civil servants of Religious Ministry of Musi Rawas District. The training variable (X2) on performance (Y) showed the tcount of 3,471> ttable 1,997 and sig 0.001 <0.05. Its means that # partially training variables had a significant influence on the performance of Civil Servants of Religious Ministry of Musi Rawas District. This showed the proven the research hypothesis and the hypothesis was accepted. Testing of the hypothesis obtained Fcount = 84.289> Ftable = 3.14 with significant level sig = 0,000 <α = 0.05. This illustrated the existence of significant influence, so it could be said that furouning competence and training significantly influenced the performance of Civil Servants of Religious Ministry of Musi Rawas District. This proved that hypothesis in this research was proven and acceptable.